Overcoming the Odds : The Benefits of Completing College for Unlikely Graduates - Brand, Jennie E. (Book collections on Project MUSE., 2023)
"Debates about college access often do not carefully consider what is required to speak knowledgeably about the benefits of college degrees. First, we want to know what an individual's life would look like without a college education. Second, we need to consider unequal access to higher education. Who attends and completes college, and who does not? Third, we need to determine which benefits of college we consider and how diverse benefits differ across diverse graduates. Too often, the rewards valued in public and academic debate begin and end with wages. The traditional focus on wages does not capture all the life-enhancing effects of higher education. In this book, Jennie Brand assesses how a range of long-term benefits of four-year college degree completion differs across the population. Considering socioeconomic, family-level, social assistance, and civic outcomes measures, she concludes that colleges are far from failing disadvantaged students. Their returns to degrees are substantial: a college degree not only enables underprivileged students to circumvent unemployment, low-wage work, job instability, poverty, and social assistance but also increases their likelihood of engaging in civic society"--